A Feasibility Study of the WHO Digital Mental Health Intervention Step-by-Step to Address Depression Among Chinese Young Adults - Sit, Hao Fong; Hong, Ieng Wai; Burchert, Sebastian; Sou, Elvo Kuai Long; Wong, Mek; Chen, Wen; Lam, Agnes Iok Fong; Hall, Brian J. (Frontiers in Psychiatry, 2022)
Abstract Background: Chinese young adults experience barriers to mental health treatment, including the lack of treatment providers and stigma around treatment seeking. Evidence-based digital mental health interventions are promising and scalable alternatives to face-to-face treatment for this population, but lack rigorous evidence to support scale-up in China. Aim: The study was a feasibility study for a large-scale RCT of Step-by-Step, a behavioral activation-based, mental health intervention to address depression and anxiety symptoms in Chinese young adults. It sought to assess feasibility of recruitment and of delivery of Step-by-Step in a university setting, to assess acceptability of the intervention, to examine potential effectiveness. Method: An uncontrolled, feasibility trial was conducted to assess the feasibility and acceptability of Chinese Step-by-Step for Chinese university students with elevated depressive symptoms (PHQ-9 scores at or above 10) in Macao, China. Data was collected at two different time points (i.e., baseline and 8-weeks after baseline), administered via questionnaires embedded in an interventional mobile application. Participation rate and dropout rate were measured. Depressive and anxiety symptom severity, well-being, and self-defined stress were assessed. Satisfaction with the program was assessed using qualitative interview. Results: A total of 173 students were screened, 22.0% (n=38) were eligible, and 63.2% of them (n=24) started the intervention. The dropout rate by post-test was 45.8%. Results from completers showed that Step-by-Step was potentially effective in reducing depressive and anxiety symptom severity, and self-defined stress. Students were generally satisfied with the program, but also offered suggestions for continued improvement. Qualitative feedback was reported within the RE-AIM framework, covering recruitment, effectiveness, adoption, implementation, and maintenance. Amendments to the program were made according to the feedback (e.g., adding notification for new session, modify the time zone). Conclusion: A minimally guided Step-by-Step protocol and the study procedure were successfully pilot tested for use for Chinese university students. The intervention was acceptable and no adverse events were reported. The results support the potential effectiveness and feasibility of a large-scale evaluation of the program.